Model Analysis of Political Message Processing of Prabowo-Hatta and Jokowi-JK in the Indonesian Presidential Election 2014 in West Jakarta - Abdul Rahman HI (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2020)
This research analyzed the political message processing of the voters of Prabowo-Hatta and Jokowi-JK in the Presidential Election 2014 in West Jakarta. The aim was to determine the influence of systematic and heuristic political message processing in the decision of beginner voters. Also, it targeted the political message processing model in the Presidential Election 2014. Quantitative research was used by conducting a survey and heuristic-systematic model was picked as the theory. It was derived into three variables, namely heuristic process variable, systematic process variable, and decision to choose president variable,. The result showed that the decision to vote Prabowo-Hatta was influenced more by systematic than heuristic political messages. On the other hand, the decision to elect Jokowi-JK was influenced more by heuristic than systematic political messages. If Prabowo-Hatta wished to improve their voters, they could strengthen the heuristic political message (emotional message), while for Jokowi / JK, they could strengthen the systematic political message (rational message).